SOSIALISASI DAN PELATIHAN PENGOLAHAN STROBERI MENJADI PRODUK SELAI STROBERI - Suliartini, Ni Wayan Sri; Nangurman, Royanissa Julia Rahmadewi; Rahil, Arya Wardana; Nafiatun, Failman; Setiawan, Wawan (Universitas Mataram, 2024)
One of the most striking natural attractions in the Sembalun Lawang area is the strawberry garden which is a tourist attraction. The abundant agricultural produce of strawberries has not been utilized by local residents to become a processed product that adds economic value. Strawberry processing is also useful for increasing the shelf life of the product. Strawberries can be processed into strawberry jam and used in making mochi snacks. The aim of this community service activity is to increase the knowledge and skills of the Sembalun Lawang Village community in processing strawberries into strawberry jam. This activity is also an effort to increase the added value of strawberries and the selling price of strawberries during the main harvest and the high level of damage to strawberries due to the short shelf life. Socialization and training was carried out on January 24 2024 in Sembalun Lawang Village, East Lombok, involving PKK members, Karang Taruna, Strawberry Farmers, Micro, Small and Medium Enterprises. Socialization was carried out using lecture and discussion methods, while training was carried out by demonstration and making strawberry jam directly by participants. Community service activities are carried out by the Unram community service team from several faculties. The resource for socialization and training is a lecturer at the Faculty of Food Technology and Agroindustry, University of Mataram. Socialization and training activities went smoothly. Participants were very enthusiastic about taking part in the activity as shown by the many questions asked regarding techniques for making strawberry jam, shelf life, information that must be written on the label and so on. The large number of participants who attended also showed the public's high interest in knowing how to process strawberries into strawberries and making strawberry jam. The conclusion that can be drawn is that there has been an increase in the knowledge and skills of the Sembalun Lawang Village community regarding processing strawberries into strawberry jam.